CTIM-26. PHASE II TRIAL OF SURVAXM PLUS TEMOZOLOMIDE FOR NEWLY DIAGNOSED GLIOBLASTOMA. (14th November 2022) - Ahluwalia, Manmeet; Ciesielski, Michael J; Reardon, David A; Abad, Ajay; Curry, William; Wong, Eric; Peereboom, David; Figel, Sheila; Hutson, Alan; Groman, Adrienne; Withers, Henry; Liu, Song; et al.
Abstract: BACKGROUND: Newly diagnosed glioblastoma (nGBM) has dismal outcomes with survival of 15-18 months. Tumor associated "survivin" is expressed in > 95% of nGBM and targetable by SurVaxM immunotherapy. METHODS: nGBM patients (pts) were enrolled in this Phase 2 study, age ≥ 18, KPS ≥ 70, IHC confirmed surviving-expression, expression of HLA-A*02, A*03, A*11 or A*24 MHC-I alleles and residual contrast enhancement of ≤1 cm 3 by MRI. Pts were treated with standard TMZ chemoradiation followed by initiation of 4 priming doses of SurVaxM (500 mcg in emulsion with Montanide ISA 51, every 2 weeks) with 100 mcg sargramostim. Maintenance doses of SurVaxM-Montanide plus sargramostim given every 12 weeks with Adjuvant TMZ for at least 6 cycles. The primary endpoint was 70% progression free survival (PFS) at 6 mos. Primary analyses of median PFS (mPFS) and median overall survival (OS) were measured from the first immunization. Safety, tolerability, and immune responsiveness were also determined. RESULTS: 63 pts (38 males), median age, 60 years were treated at 5 sites. SurVaxM was well tolerated, with no serious adverse events. A strong positive correlation, accounting for censoring, was observed between PFS and OS of all pts (r = 0.79; 95% CI (0.66, 0.87)). SurVaxM was immunogenic and produced survivin-specific CD8+ T-cells and antibody (IgG) titers in both methylated and unmethylated MGMT pts. Both groups showed clinical benefit with PFS of 11.4 months for the for the whole group, 7.0 months for unmethylated and 17.9 months for methylated group. OS of 25.9 months for the whole group, 16.5 months for unmethylated and 41.4 months for methylated group. CONCLUSIONS: SurVaxM appeared to be safe and well-tolerated in pts with nGBM. SurVaxM was effective at stimulating survivin-specific immune responses and the primary endpoint was met. SurVaxM represents a promising therapy for nGBM, randomized trial is ongoing. Clinical trial information: NCT02455557.